Pharmaceutical Installation Performance Analysis PKU Muhammadyah RSU Sragen with a Balance Scorecard Approach - Setyawan, Indra Agus; Kusumawati, Wiwik; Harimurti, Sabtanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Research objectives: To determine the performance of the pharmaceutical installation of PKU Muhammadiyah Hospital Sragen based on a learning and growth perspective, which is viewed from job satisfaction, worker retention, work productivity and job training. Research Methods: This type of research is descriptive research with a quantitative approach. The sample used was 18 employees of the pharmacy installation of PKU Muhammadiyah Hospital Sragen according to the established criteria. Data analysis uses frequency distribution which is presented in tabular form. Research Results: Employee performance in terms of job satisfaction is included in the fairly satisfied category, meaning that employees are satisfied with income other than salary, promotions, co-workers, superiors to their work. Employee performance as seen from employee retention from 2017 to 2020 has the ability to keep employees from working in hospitals. Employee performance as seen from the training does not meet the training target, which is a minimum of two trainings per year. Approximately 61.11% or 11 employees who have attended training. Employee performance seen from productivity, the income earned by employees from 2017 to 2019 did not experience a significant change Abstrack: Tujuan penelitian: Untuk mengetahui kinerja instalasi farmasi RS PKU Muhammadiyah Sragen berdasarkan perspektif pembelajaran dan pertumbuhan, yang ditinjau dari kepuasan kerja, retensi pekerja, produktivitas kerja dan pelatihan kerja. Metode Penelitian: Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kuantitatif. Sampel yang digunakan yaitu 18 orang karyawan instalasi farmasi RS PKU Muhammadiyah Sragen sesuai dengan kriteria yang ditetapkan. Analisis data menggunakan distribusi frekuensi yang disajikan dalam bentuk tabel. Hasil Penelitian: Kinerja karyawan dilihat dari kepuasan kerjanya termasuk dalam kategori cukup puas, artinya karyawan merasa puas terhadap pendapatan selain gaji, promosi, rekan kerja, atasannya hingga pekerjaannya. Kinerja karyawan yang dilihat dari retensi pekerja sejak tahun 2017 hingga tahun 2020 memiliki kemampuan untuk menahan karyawannya agar tetap bekerja di rumah sakit. Kinerja karyawan yang dilihat dari pelatihan tidak memenuhi target pelatihan, yaitu minimum dua kali pelatihan setiap tahunnya. Sekitar 61,11% atau 11 orang karyawan yang sudah pernah mengikuti pelatihan. Kinerja karyawan yang dilihat dari produktivitasnya, pendapatan yang diperoleh karyawan dari tahun 2017 hingga 2019 tidak mengalami perubahan yang signifikan. Kesimpulan: Kinerja karyawan dalam prespektif pembelajaran dan pertumbuhan secara keseluruhan termasuk cukup baik.